2008
DOI: 10.1097/coh.0b013e328302cc3d
|View full text |Cite
|
Sign up to set email alerts
|

Ocular immune reconstitution inflammatory syndromes

Abstract: Immune recovery uveitis is the most common form of immune reconstitution inflammatory syndrome in HIV-infected patients with cytomegalovirus retinitis who are receiving highly active antiretroviral therapy. Clear clinical definitions are required for ocular immune reconstitution inflammatory syndromes to avoid misclassification of other inflammatory conditions. A multidisciplinary approach is important in the diagnosis and management of immune recovery uveitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 39 publications
(48 reference statements)
0
22
0
Order By: Relevance
“…The herein reported high HHV seroprevalence and consequently high risk for HHV-related diseases among HIV-infected individuals warrant increased awareness among healthcare workers in rural South Africa for early clinical signs of these conditions to initiate prompt antiviral treatment: e.g. early diagnosis and treatment of herpes zoster ophthalmicus to prevent corneal blindness [4], [6]. In conclusion, seroprevalence of HHVs in rural South Africa is very high and recognition and awareness of HHV-related diseases is warranted.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…The herein reported high HHV seroprevalence and consequently high risk for HHV-related diseases among HIV-infected individuals warrant increased awareness among healthcare workers in rural South Africa for early clinical signs of these conditions to initiate prompt antiviral treatment: e.g. early diagnosis and treatment of herpes zoster ophthalmicus to prevent corneal blindness [4], [6]. In conclusion, seroprevalence of HHVs in rural South Africa is very high and recognition and awareness of HHV-related diseases is warranted.…”
Section: Discussionmentioning
confidence: 74%
“…Even after the introduction of antiretroviral therapy (ART), HIV-infected individuals remain at risk of developing severe HHV-related diseases as ART-induced recuperation of adaptive immunity may result in vigorous anti-HHV cellular immune responses. In the case of residual ocular CMV infection, restored CMV immunity may lead to sight-threatening immune recovery uveitis [6]. HHV infections clinically interact with HIV, contribute substantially to hospitalization, morbidity and mortality and some HHVs (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…This may have resulted in selection bias due to ineffective referral of uveitis cases from primary healthcare facilities to hospitals. It is also likely that mild uveitis cases were missed at primary healthcare level and therefore not presented to the hospital, including cases of immune recovery uveitis as this condition is usually asymptomatic or self-limiting if symptomatic 22. Another limitation of our study is that diagnostic aspiration of AH was not obtained from all study participants.…”
Section: Discussionmentioning
confidence: 97%
“…Immune recovery uveitis is a known ocular entity occurring due to immune reconstitution following HAART. 6,7 Studies have reported a high risk of occurrence of TEN or SJS in AIDS patients on nevirapine, [8][9][10][11] which is mainly due to the immune reconstitution resulting in an accelerated inflammatory response. 12,13 All 3 cases that presented to us developed the characteristic skin lesions suggestive of SJS and TEN within a few weeks of initiation of HAART.…”
Section: Discussionmentioning
confidence: 97%